Axillary buds are dwarfed shoots that tightly regulate GA pathway and GA-inducible 1,3-β-glucanase genes during branching in hybrid aspen - Rinne, Päivi L.H. (J Exp Bot, 2016)
Axillary buds (AXBs) of hybrid aspen (Populus tremula×P. tremuloides) contain a developing dwarfed shoot that becomes para-dormant at the bud maturation point. Para-dormant AXBs can grow out after stem decapitation, while dormant AXBs pre-require long-term chilling to release them from dormancy. The latter is mediated by gibberellin (GA)-regulated 1,3-β-glucanases, but it is unknown if GA is also important in the development, activation, and outgrowth of para-dormant AXBs. The present data show that para-dormant AXBs up-regulate GA receptor genes during their maturation, but curtail GA biosynthesis by down-regulating the rate-limiting GIBBERELLIN 3-OXIDASE2 (GA3ox2), which is characteristically expressed in the growing apex. However, decapitation significantly up-regulated GA3ox2 and GA(4)-responsive 1,3-β-glucanases (GH17-family; α-clade). In contrast, decapitation down-regulated γ-clade 1,3-β-glucanases, which were strongly up-regulated in maturing AXBs concomitant with lipid body accumulation. Overexpression of selected GH17 members in hybrid aspen resulted in characteristic branching patterns. The α-clade member induced an acropetal branching pattern, whereas the γ-clade member activated AXBs in recurrent flushes during transient cessation of apex proliferation. The results support a model in which curtailing the final step in GA biosynthesis dwarfs the embryonic shoot, while high levels of GA precursors and GA receptors keep AXBs poised for growth. GA signaling, induced by decapitation, reinvigorates symplasmic supply routes through GA-inducible 1,3-β-glucanases that hydrolyze callose at sieve plates and plasmodesmata.